Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2020)
A dataset containing 341 species occurrences available in GBIF matching the query: { "and" : [ "Geometry POLYGON((-74.96509 38.96585,-74.97453 38.93941,-74.96595 38.92774,-74.91788 38.92619,-74.86844 38.94164,-74.87531 38.95228,-74.90243 38.95211,-74.9129 38.95795,-74.93642 38.9667,-74.96509 38.96585))", "TaxonKey is Lepidoptera" ] } The dataset includes 341 records from 12 constituent datasets: 1 records from C.A. Triplehorn Insect Collection (OSUC), Ohio State University. 1584 records from iNaturalist Research-grade Observations. 30 records from The Lepidopterists' Society Season Summary. 1 records from Biodiversity4all Research-Grade Observations. 2 records from The Albert J. Cook Arthropod Research Collection. 12 records from naturgucker. 8 records from C.P. Gillette Museum of Arthropod Diversity. 34 records from Museum of Comparative Zoology, Harvard University. 1 records from University of Delaware Insect Research Collection. 220 records from Entomology Division, Yale Peabody Museum. 744 records from Monarch Watch. 4 records from International Barcode of Life project (iBOL). Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences